Children in institutional re-socialisation and education – on the edge of contemporary trends - Justyna Kusztal; Sławomir Przybyliński (Problemy Wczesnej Edukacji)
This article analyses the situation of a child placed in an isolation facility in the context of contemporary trends in treating children and adolescents by the judiciary and in educational and resocialisation facilities. The system of juvenile re-socialisation in Poland, regulated by the Act on Juvenile Delinquency Proceedings of 1982, covers children and adolescents in connection with their depravation or with committing a punishable offence and it provides for institutional educational measures and reformatory measures in the form of sending a minor to a juvenile detention centre. Although a prison sentence passed on minors is an exception to the rule of adjudicating educational and reformatory measures, according to international regulations, the category of juvenile imprisonment is broader than serving a sentence in prison. It is our intention to consider the situation of a child placed outside their home in an institution where they are exposed to confinement by a court or another administrative body.